Katsambekis, G. and Kioupkiolis, A. (Eds.) (2019). The populist radical left in Europe. Routledge (228 pages). ISBN: 9780367731175. - Spyropoulou, Vivian (The Greek Review of Social Research, 2024)
Ν/Α